Tonsil histopathology in HIV-infected versus HIV-uninfected adults - Ridwaan Essa; Shivesh Maharaj; Kapila Hari; Shahpar Motakef (Southern African Journal of HIV Medicine, 2019)
Background: The relationship between HIV and tonsil malignancy has not been fully investigated and established. Both of these diseases prominently feature in the Otorhinolaryngology clinics.